Recall that:
The power series for 1/(1-x)11−x is sum_(n=0)^N x^nN∑n=0xn.
What you can do is take the derivative of both sides:
d/(dx)[sum_(n=0)^N x^n] = d/(dx)[1/(1-x)] = color(green)(d/(dx)[1 + x + x^2 + ...])
When we take the derivative, note that the first term will disappear (d/(dx)[1] = 0), so the first n shifts from n=0 to n=1.
sum_(n=1)^N nx^(n-1) = 1/(1-x)^2 = color(green)(?)
We can shift it back to n = 0 for conventional purposes.
How you do that is consider that you are currently starting at n=1. That means n-1 = 0. To get the exponent to become 0 using n = 0 below sum, n-1 becomes n.
When n = 1 below sum, nx^(n-1) starts at 1x^0, so when n = 0 below sum, nx^"stuff" becomes (n+1)x^"stuff".
color(highlight)(sum_(n=0)^N (n+1)x^(n) = 1/(1-x)^2) = color(green)(?)
So, all we need to do is do it for the explicit series to get:
1/(1-x)^2 = d/(dx)[1 + x + x^2 + ...]
= color(blue)(1 + 2x + 3x^2 + 4x^3 + ...)
The radius of convergence is based on the idea that the sum of magnitudes |a| >= 1 will not converge if they are all positive.
1/(1-x)^2 > 1 when |x| >= 1.
Therefore, the radius of converge is:
color(blue)(x in (-1, 1))
or you can write it as:
color(blue)(|x| < 1)